2015
DOI: 10.4238/2015.october.21.2
|View full text |Cite
|
Sign up to set email alerts
|

Matrilineage differentiation of the genus Tetragonisca using mitochondrial DNA markers and the polymerase chain reaction-restriction fragment length polymorphism technique

Abstract: ABSTRACT. The Meliponinae are important pollinators of plant species, and one of the most managed species is Tetragonisca angustula. Initially, two subspecies were identified in T. angustula: T. angustula angustula and T. angustula fiebrigi. Subsequently, T. a. fiebrigi was considered a species, based on the coloration of its mesepisternum. The objective of the present study was to obtain genetic markers that could differentiate the two species by amplifying regions of mitochondrial DNA and conducting polymera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 19 publications
1
9
0
Order By: Relevance
“…The results of our study were consistent with those reported by Santos et al (2015), as the Tetragonisca samples amplified for the ND2, COI (primer 1) region, approximately 2,400 bp in size, and cleavage occurred using the same restriction enzymes (EcoRI and EcoRV) in T. angustula from the state of Rondônia, except for the cleavage using the RsaI enzyme, which occurred only in T. weyrauchi.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The results of our study were consistent with those reported by Santos et al (2015), as the Tetragonisca samples amplified for the ND2, COI (primer 1) region, approximately 2,400 bp in size, and cleavage occurred using the same restriction enzymes (EcoRI and EcoRV) in T. angustula from the state of Rondônia, except for the cleavage using the RsaI enzyme, which occurred only in T. weyrauchi.…”
Section: Discussionsupporting
confidence: 91%
“…The 1,850-bp fragment resulted from the amplification of (COI) primer 2 region observed in T. angustula and T. weyrauchi was also observed by Santos et al (2015) in T. angustula and T. fiebrigi. However, these authors observed the cleaving of this region using two restriction enzymes (EcoRV and HinfI).…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…While Tetragonisca angustula (Latreille, 1811) occurs in practically all Brazilian regions, Tetragonisca fiebrigi [Schwarz, 1938] has a more central-to-south distribution [Camargo and Pedro, 1836]. The taxonomic status of these two species is still discussed, and several authors have called attention to the possibility of hybridization between them Contel, 1995, 2005;Koling and Moretto, 2010;Francisco et al, 2014;Santos et al, 2015;Kulza et al, 2022].…”
Section: Introductionmentioning
confidence: 99%